-9*x-2*x-18=26

Simple and best practice solution for -9*x-2*x-18=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9*x-2*x-18=26 equation:


Simplifying
-9x + -2x + -18 = 26

Reorder the terms:
-18 + -9x + -2x = 26

Combine like terms: -9x + -2x = -11x
-18 + -11x = 26

Solving
-18 + -11x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + -11x = 26 + 18

Combine like terms: -18 + 18 = 0
0 + -11x = 26 + 18
-11x = 26 + 18

Combine like terms: 26 + 18 = 44
-11x = 44

Divide each side by '-11'.
x = -4

Simplifying
x = -4

See similar equations:

| 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | q^2+4q+4=26 | | 6-+4=210 | | 3x+20=5-16 | | (3x-4)(x-3x+2)= | | x/30=9 | | 16=s-p | | 12v^2+12v-15=0 | | 72-4.9t^2=8t | | 4x-4=-48 | | 3/10+7/10 | | 0-600*2-600*2+X*2-0.2X*4=0 | | a^2-a-8=0 | | 7/10+1/5 | | 4x+7-3x=15 | | -4n+2+3n=8-n+6 | | 5/12+5/12 | | 2x-1/2(3x-2)=7/4-x | | 0=18x^2 | | X-22=15 | | -6-8=9x+7-8x | | -x^2-23x-60=0 | | 17/19+1/19 | | w/4=13 | | -3+21=m-8 |

Equations solver categories